2002
DOI: 10.1128/iai.70.6.2965-2975.2002
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus ducreyi Requires the flp Gene Cluster for Microcolony Formation In Vitro

Abstract: Haemophilus ducreyi, the etiologic agent of chancroid, has been shown to form microcolonies when cultured in the presence of human foreskin fibroblasts. We identified a 15-gene cluster in H. ducreyi that encoded predicted protein products with significant homology to those encoded by the tad (for tight adhesion) locus in Actinobacillus actinomycetemcomitans that is involved in the production of fimbriae by this periodontal pathogen. The first three open reading frames in this H. ducreyi gene cluster encoded pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 54 publications
(52 reference statements)
4
76
0
Order By: Relevance
“…Nevertheless, the widespread existence of the tad locus (Kachlany et al 2000;Bhattarcharjee et al 2001;Nika et al 2002;de Bentzmann et al 2006). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the widespread existence of the tad locus (Kachlany et al 2000;Bhattarcharjee et al 2001;Nika et al 2002;de Bentzmann et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…actinomycetemcomitans (Schreiner et al 2003), Haemophilus ducreyi (Nika et al 2002;Spinola et al 2003), Yersinia ruckeri (Fernandez et al 2004) and Pasteurella multocida (Fuller et al 2000). In contrast to these human and animal pathogenic bacteria, the functional significance of the tad locus in phytopathogenic bacteria has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence assay. Adherence of H. ducreyi cells to U-937 macrophages was evaluated with a modified version of a previously described attachment assay (38). The differentiation of the U-937 cells was induced as described above at 2 ϫ 10 5 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…A newly described subtype of T2SS, tad locus (tight adherence) (Tomich et al, 2007) was identified in all six genomes. The tad locus encodes the machinery required for the assembly of adhesive Flp (fimbrial low-molecule-weight protein) pili and is necessary for bacterial adhesion to surfaces, biofilm formation, and pathogenesis as shown for Aggregatibacter actinomycetemcomitans (Planet et al, 2003), Haemophilus (Nika et al, 2002), Pseudomonas (Durand et al, 2003), Yersinia etc. (Tomich et al, 2007).…”
Section: Secretion Systemsmentioning
confidence: 99%